Analisis Strategi Advokasi Gerakan Mahasiswa Nasional Indonesia (GMNI) Jakarta Selatan pada Warga Terdampak Penggusuran di Kebon Sayur, Cengkareng - Giras Jagratara; Mohammad Rafatta Umar; Muhammad Dzikra Gunawan (Universitas Wijaya Kusuma Surabaya, 2026)
This study examines the advocacy strategies of the South Jakarta branch of the Indonesian National Student Movement (GMNI) in assisting residents affected by forced evictions in Kebon Sayur, Cengkareng. The research emerges from the increasing number of urban agrarian conflicts, which often reveal unequal power relations between residents and capital-backed actors. It aims to identify the forms of advocacy strategies implemented by GMNI and to explain how the organization responds to restricted access to formal justice mechanisms. Using a qualitative case study approach, the research draws on in-depth interviews, field observations, and document analysis. The findings show that GMNI develops an advocacy strategy grounded in Political Opportunity Structure theory by leveraging political dynamics and elite fractures to push for government intervention. The organization also reframes the eviction issue, shifting the narrative from a strictly legal-administrative matter to a humanitarian concern. In addition, GMNI strengthens community capacity through an educational community center designed to foster critical awareness and grassroots self-reliance. The study concludes that an advocacy strategy that integrates political context analysis, narrative construction, and community empowerment can strengthen the position of vulnerable groups in urban agrarian conflicts. However, GMNI still needs to optimize its digital campaigning strategy to broaden public support